Intervensi yang Efektif dalam Peningkatan Skrining Kanker Serviks pada Perempuan Usia Subur - Kurniawati, Pindi kurniawati; Setyowati, Setyowati; Rachmawati, Imami Nur (Journal of Telenursing (JOTING), 2024)
This study aims to review the literature on effective interventions to increase the uptake of cervical cancer screening in women of childbearing age. The method used is a systematic review through searching for articles according to the formulation of research questions using the PIO formula in the Proquest, Pubmed, Sage Journal, Science Direct, and Scopus databases. The search keywords used are ((technology[Title/Abstract]) OR (innovation[Title/Abstract])) OR (intervention[Title/Abstract])) OR (method[Title/Abstract])) AND (increase cervical cancer screening[Title/Abstract])) OR (improve cervical cancer screening[Title/Abstract]). The results showed that from 10 articles reviewed, relevant interventions were found to increase screening uptake, including the provision of SMS (education and reminder) and eVouchers, self-sampling of HPV sent by post, FCHV visits to provide education and counseling using flipchart media and booklets as well as talk shows and peer discussions by CHW. CHW conducts education using video clips and brochures, Conclusions, and relevant interventions to increase the uptake of cervical cancer screening are the provision of reminder messages and eVouchers, self-sampling of HPV sent by post, mentoring interventions by FCHV or CHW for education and counseling. Keywords: Technology Intervention, Cervical Cancer Screening, Women of Childbearing Age